Reading Arab women's autobiographies : Shahrazad tells her story - Golley, Nawar Al-Hassan, 1961- (University of Texas Press, 2003)
The author applies a number of Western critical theories to Arab women's autobiographical works, including Marxism, feminism, colonial discourse & narrative theory, & at the same time interrogates these theories against chosen texts to test their adequacy for analysis of writings from other cultures.